DECISION MAKING KEPALA MADRASAH DALAM MENGELOLA PEMBELAJARAN MASA COVID-19 DI MADRASAH DINIYAH AL-AMIRIYAH - Muh Imam Khaudli; Nurul Bariroh Hafidz (Institut Agama Islam Darussalam Blokagung, 2021)
Dacision making in educational institutions is one of the duits of the head of educatiol institutons, including decision making in terms of learning management held in educational institutions.Decision making is taken according to the surrounding conditions. In 2020, indonesia was shocjed by the covid-19 outbreak that originated in Wuhan.Due to the Covid-19 outbreak, educational institutions had to stop their teaching and learnng.This madrasah diniyah Al-Amiriyah is an educational institution with the most students at the Darussalam Islamic boarding school foundation, wich during the covid-19 pandemic season. Teaching and learning activities continud without compromising it’s quality. In this study, the focus of research is on what decision are taken and how they are implemented in learning management. In this study, researchers used qualitative methods in the problem-solving process wich used interviews, observations, and documentatry studied as data colletion techniques and used trigulation that ulitized sources as the validity of the data.